Design program for Kombolcha Campus site - Karlsson, Ida; Philipsen, Josephine (2014)
The objective for this Masters thesis is to conduct a Design program, as a planning and design tool, for the outdoor environment at the campus site of Wollo University in Kombolcha, located in northern Ethiopia. The geographical location as well as the social and political context of the site has constituted the framework for this Design program and Masters thesis. Kombolcha Campus site was established during 2006/2007, as part of the Ethiopian government’s strategy for higher development which was initiated in the Ethiopian policy of ‘Education and training’ 2001. Investment in higher education was a step towards the development of socio-economic conditions and an essential prerequisite for poverty reduction and important for the future of Ethiopia (Federal ministry of Education, 2010). The strategy has resulted in several universities being built during the last decade distributed in different parts of Ethiopia.